Investigation of the through-process (sub)surface condition of Dual Phase grades for the understanding of temperature deviation in Galvanizing Line 3 of Tata Steel IJmuiden - Τόκη, Χριστίνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Θαλάσσιων Κατασκευών, 2018)
Dual Phase steel is part of the Advanced High Strength Steels (AHSS) family, that combine outstanding strength along with great formability due to their microstructure, comprising of a soft ferritic matrix with islands of a harder phase (martensite/bainite). Their properties have rendered them very attractive, especially to the automotive industry, and research has been dedicated to their continuous improvement. To accomplish the production of successful products that meet both, the requirements of properties and the requirements of the finish surface, it is crucial to monitor and control the most important factors of every process. Tata Steel IJmuiden has developed a model predictive control system called Optimal Strip Continuous Annealing Regulator (OSCAR) to control the temperature response of the strip in Galvanizing Line 3 (DVL3). OSCAR has been successfully implemented on the production of conventional steel grades, but exhibits temperature deviations in the case of Dual Phase grades.The aim is to identify the differences between them and correlate them with the process parameters applied to them during production and the alloying content of the grade.